International Class Program UIN Malang as an Effort in Actualizing International Reputable University - Nikmah, Faridatun; Syari'ah, Atiris; Nabilah, Nafa (Pascasarjana IAIN Kudus, 2023)
In response to globalization's challenges, educational institutions in Indonesia have begun to develop education oriented towards reforming quality, management, and curriculum with international standards. One of them is through the formation of an international class that is expected to be able to compete at the global level. To realize this, UIN Malang carries the vision of